(untitled) (International Journal of Environmental Sciences, 2025)
Background Maternal age is a critical determinant of pregnancy outcomes. Adolescents and young adult women are considered a high-risk group due to the increased incidence of both maternal and perinatal complications. Teenage pregnancies, in particular, are associated with elevated risks of fetal and infant morbidity and mortality, as highlighted by the World Health Organization (WHO). Adverse outcomes among young mothers may include anemia, pre-eclampsia, eclampsia, preterm delivery, low birth weight, and perinatal death.